Psychometric Properties of the Korean Family Reported Outcome Measure for Family Members of Patients With Acquired Brain Injury. Issue 6 (December 2021) - Oh, Hay Young; Shin, Yong Soon
Abstract : ABSTRACT: BACKGROUND: Acquired brain injury (ABI) affects not only survivors but also their family members' quality of life in various ways. The Family Reported Outcome Measure (FROM-16), a self-reported instrument, has been developed to evaluate the impact of diseases on the lives of family members of patients. This study aimed to assess the reliability and validity of the Korean FROM-16 for family members of individuals with ABI. METHODS: A total of 200 family members of patients with ABI in South Korea participated in this study. Internal consistency was assessed using Cronbach α . To establish the validity, we evaluated the semantic equivalence, content, known-group, conduct, concurrent, and convergent validity of the Korean FROM-16. For exploratory factor analysis, common factor analysis with oblique rotation, parallel analysis, an eigenvalue greater than 1.0, and a scree plot were used. RESULTS: Exploratory factor analysis revealed 2 factors for the 16 items, which explained 67.4% of the total variance. Concurrent validity was established by comparison with the Korean World Health Organization Quality of Life Scale Brief ( r = −0.57), and regarding the convergent validity, the Korean FROM-16 score positively correlated with the Korean Neurobehavioral Functioning Inventory. Known-group validity was confirmed by showing that family members with advanced age, the burden of caring, and insufficient income, as well as spouses, had a statistically higher score in the Korean FROM-16. Cronbach α was .92, indicating high internal consistency reliability. CONCLUSION: The Korean FROM-16 is a valid and reliable instrument for evaluating the impact of diseases on family members of individuals with ABI in South Korea. Abstract : Supplemental digital content is available in the text.